2020
DOI: 10.3389/fimmu.2020.00931
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inflammation by Extracellular Granzyme A

Abstract: Granzyme A (GrA) has long been recognized as one of the key players in the induction of cell death of neoplastic, foreign or infected cells after granule delivery by cytotoxic cells. While the cytotoxic potential of GrA is controversial in current literature, accumulating evidence now indicates roles for extracellular GrA in modulating inflammation and inflammatory diseases. This paper aims to explore the literature presenting current knowledge on GrA as an extracellular modulator of inflammation by summarizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 100 publications
1
47
0
Order By: Relevance
“…Although granzymes are traditionally described as primarily being involved in immune-targeted cell death, emerging clinical and biochemical evidence suggests additional roles for granzymes (5,6). For example, GrB acts in autoimmune diseases by directly cleaving or aiding in the production of autoantigens (7). Additionally, various granzymes (GrA, GrB, GrM) are reported to induce inflammation and interfere in viral replication (3,(8)(9)(10) and all human granzymes target hnRNP K which reduces tumour cell viability (11).…”
Section: Introductionmentioning
confidence: 99%
“…Although granzymes are traditionally described as primarily being involved in immune-targeted cell death, emerging clinical and biochemical evidence suggests additional roles for granzymes (5,6). For example, GrB acts in autoimmune diseases by directly cleaving or aiding in the production of autoantigens (7). Additionally, various granzymes (GrA, GrB, GrM) are reported to induce inflammation and interfere in viral replication (3,(8)(9)(10) and all human granzymes target hnRNP K which reduces tumour cell viability (11).…”
Section: Introductionmentioning
confidence: 99%
“…6b), with NK cells the likely source of GzmA (Schanoski et al, 2019). RNA-Seq analyses comparing GzmA S211A with 6J mice support the view that circulating proteolytically active GzmA (Table 1) promotes certain immune-stimulating and proinflammatory activities (Schanoski et al, 2019;Shimizu et al, 2019;van Daalen et al, 2020;Wensink et al, 2015), with STAT6, STAT3, NFATC2, JUN, NFKB1 and STAT1 identified as dominant USRs (Fig. 6b.…”
Section: Gzma's Bioactivity After Chikv Infection and Poly(i:c) Treatmentmentioning
confidence: 57%
“…Like granzyme B (GzmB), GzmA has thus been classified as a cytotoxic granzyme (Golstein and Griffiths, 2018;Mpande et al, 2018;Muraro et al, 2017;Zhou et al, 2020), although in several studies a role for GzmA in mediating cellular cytotoxicity was not observed (Ebnet et al, 1995;Joeckel and Bird, 2014;Regner et al, 2009;Regner et al, 2011;Smyth et al, 2003). In a range of settings GzmA has also been associated with the promotion of inflammation, providing an additional or alternative view of its physiological role, although consensus on mechanisms has remained elusive (Metkar et al, 2008;Park et al, 2020;Santiago et al, 2020;Santiago et al, 2017;Schanoski et al, 2019;Shimizu et al, 2019; van Daalen et al, 2020;Wensink et al, 2015;Wilson et al, 2017), with a number of potential intracellular and extracellular targets for GzmA reported. These include pro-IL-1β (Hildebrand et al, 2014), SET complex proteins (Mandrup-Poulsen, 2017;Mollah et al, 2017), gasdermin B (Zhou et al, 2020), mitochondrial complex I protein NDUFS3 (Martinvalet et al, 2008), protease activated receptors (Hansen et al, 2005;Sower et al, 1996;Suidan et al, 1994;Suidan et al, 1996), TLR2/4 (van Eck et al, 2017) and TLR9 (Shimizu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the only likely TEM-stimulating proteases activating PAR1 in our experimental setup could be granzymes, chymase and kallikreins ( Table 1 ). All three proteases may conceivably play a role in lymphocyte TEM: Granzymes are abundantly present during tissue remodelling in chronic inflammation [ 32 ]. Classically, they are recognised to play a key role in the induction of lymphocyte-induced cell death including that of neurons during neuroinflammation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%